Influence of aged Ti-15V-3Cr-3Sn-3Al alloy microstructure on chemical and electrochemical behavior in the Kroll reagent for metallographic etching - Ribeiro, Rosinei B. [UNESP] (2003)
The chemical and electrochemical behaviour of the Ti-15V-3Cr-3Sn-3Al alloy in Kroll reagent has been studied after ageing at 350-600°C, to optimise metallographic etching. Etching tests and polarisation curves showed that samples aged at higher temperatures have been more susceptible to corrosion. It has been attributed to the formation of intra- and intergranular α-phase precipitates during ageing.